Kajian Gender Leadership And Inequality Pada Perguruan Tinggi Di Indonesia - Iswachyu Dhaniarti; Ani Wulandari; M. Ikhsan Setiawan (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Ministry of Women Empowerment and Child Protection of Indonesia (2013), said that although Indonesia, Laos, and Cambodia has taken various gender equality programs, three countries including countries with high gender inequality index. This suggests that men are still dominant in each of the indicators, better employment, education and representation in parliament. The importance of decision-making on women's issues has been recognized within the framework of the millennium development goals. One of the indicators for monitoring the Millennium Development Goal 3 on gender equality. Research McKinsey and Company (2008) in his book entitled Women Matter 2 shows that having more women leaders ranks of upper management position can give companies a real competition atmosphere. One of the requirements of skills for a leader who can become a benchmark for the effectiveness of leadership is decision-making. Based on this, an organization can run productive and effective if the leader can be agile, intelligent, quick and thoughtful in making decisions. Research conducted at the University of Narotama, Surabaya, while for survey and data collection is done at the Research and Technology Ministry of Higher Education (PT in Indonesia) and Kopertis VII East Java (East Java PTS). More women leaders positioned above the management of Higher Education is expected to provide real competition atmosphere. One of the requirements of skills for a leader who can become a benchmark for the effectiveness of leadership is decision-making. Universities can run productive and effective if the leader can be agile, intelligent, quick and thoughtful in making decisions. The impact is the increased ranking Universities with the Rector of Women, in the classification and ranking of PT Ministry of Research and Technology of Higher Education as a description of continuous improvement and health organizations in implementing tri-dharma